Expected impacts of climate change threaten the anuran diversity in the Brazilian hotspots - Vasconcelos, Tiago S. [UNESP]; Nascimento, Bruno T. M. do [UNESP]; Prado, Vitor H. M. (Wiley-Blackwell, 2018)
We performed Ecological Niche Models (ENMs) to generate climatically suitable areas for anurans in the Brazilian hotspots, the Atlantic Forest (AF), and Cerrado (CER), considering the baseline and future climate change scenarios, to evaluate the differences in the alpha and beta diversity metrics across time. We surveyed anuran occurrence records and generated ENMs for 350 and 155 species in the AF and CER. The final predictive maps for the baseline, 2050, and 2070 climate scenarios, based on an ensemble approach, were used to estimate the alpha (local species richness) and beta diversity metrics (local contribution to beta diversity index and its decomposition into replacement and nestedness components) in each similar to 50x50 km grid cell of the hotspots. Climate change is not expected to drastically change the distribution of the anuran richness gradients, but to negatively impact their whole extensions (i.e., cause species losses throughout the hotspots), except the northeastern CER that is expected to gain in species richness. Areas having high beta diversity are expected to decrease in northeastern CER, whereas an increase is expected in southeastern/southwestern CER under climate change. High beta diversity areas are expected to remain in the same AF locations as the prediction of the baseline climate, but the predominance of species loss under climate change is expected to increase the nestedness component in the hotspot. These results suggest that the lack of similar climatically suitable areas for most species will be the main challenge that species will face in the future. Finally, the application of the present framework to a wide range of taxa is an important step for the conservation of threatened biomes.
Keywords: alpha diversity; amphibia; Atlantic Forest; beta diversity; Cerrado; macroecology